A Dual‐Reactor Concept for the High‐Yielding Conversion of Methane into Higher Hydrocarbons. Issue 3 (9th January 2013) - Kondratenko, Evgenii V.; Rodemerck, Uwe
<x xml:space="preserve">Abstract</x> Dual to the death: The selective conversion of methane into higher alkanes in industrially relevant conversions combines the oxidative coupling of methane (OCM) with the selective hydrogenation of CO and CO2 in a second reactor, without the need for expensive pre‐separation of the reaction products that are formed in the OCM reactor. Thus, the yield of higher alkanes (34 %) is at least 50 % higher than that from a single OCM reactor.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>